Biomechanical testing to evaluate the cut-through resistance of intramedullary nails for the proximal humerus. (December 2016) - Wanzl, Maximilian; Foehr, Peter; Schreiber, Ulrich; Burgkart, Rainer H.; Lenich, Andreas
Abstract: Intramedullary nailing for stabilization of proximal humeral fractures is well-established. Complications as part of a cut-through, such as backing out of locking screws, loss of reduction, and perforation of the screws into the glenoid, are equally well-known. The test bench presented in this study enables testing of the cut-through behavior of multiple intramedullary implants on a simulated osteoporotic three-part fracture configuration with three different loading circumstances (A, B and C). In situation A, the glenohumeral dynamic force with progressive loadings entered at an angle of 15° to the humeral shaft. In situation B the force entered at an angle of 35° and in situation C the angle measured 55°. Three different types of nails were tested: the Targon PH with the optimal proximal screw length (T) and with all four proximal screws shortened (Tshort), the Synthes MultiLoc PHN with (S5) and without (S4) the additional calcar screw and, lastly, the PolyAxNail PH, a polyaxial intramedullary nail, in a neutral screw configuration (PAN) and a version with diametrically opposed crossed first and fourth locking screws (PAN10). Significant differences in the three cases were found with the evaluation of the failure load, which represents the cut-through resistance. Case A: Tshort (245.4 ± 18.7 N) – S4 (346.8 ± 18.0 N) (adjusted p = 0.002); Tshort (245.4 ± 18.7 N) – S5 (368.5 ± 12.0 N) (adjusted p = < 0.001); Tshort (245.4 ± 18.7 N) – T (323.5 ± 38.2 N) ( p = 0.004); Case B: no significant differences between the study groups (adjusted significance). Case C: PAN (412.5 ± 16.0 N) – S5 (471.5 ± 21.5 N) (adjusted p = 0.007); T (414.0 ± 33.5 N) – S5 (471.5 ± 21.5 N) (adjusted p = 0.008). The optimal screw length has a strong influence on the failure load. Choosing proximal screws that are too short, produces a negative impact on the cut-through resistance. The additional calcar screw of the MultiLoc PHN and the polyaxiality of the PolyAxNail showed a positive effect with regard to the failure load reached.